PEMBENTUKAN KOSAKATA BAHASA ARAB OLEH SANTRI PONDOK MODERN DARUSSALAM GONTOR - Hisyam Zaeni (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
The differences of Arabic and Indonesian language as well as the imposition of a learning system that requires students to communicate in Arabic in any time results in many mistakes while practicing the language among the students of Modern Islamic Boarding School of Gontor, especially in term of vocabulary. Such mistaken language is a unique one, because it creates a style of their own new language. Therefore, this study is conducted that focuses on the vocabulary formation. Synchronic linguistic approach to the theory of contrastive morphology modern Arab-Indonesia in particular phonemes that are strengthened by data analysis methods and percieving (observation) is used to analyze the common daily language of the students. The study results showed that the formation of a new vocabulary that differs from the recognized rules of Arabic is divided into two, namely internal (lexical shape changes which is still in the category of Arabic language) and external (lexical form changes which come under the category of Indonesian language). While the changing of vocabulary includes nouns and verbs.